Contribution of Organic Farming for Achieving the Objectives of Sustainable Agriculture - Ovidia Ramona POPA; Raluca Andreea ION (Revista de Management Comparat International)
Organic farming supports sustainable agriculture and connects not only food requirements in an environmentally friendly way, but also future requirements to fight climate change. Organic production is an agricultural system that combines biodiversity, good environmental and climate action practices, high animal welfare standards and conservation of natural resources. The objectives of the research are to identify the contribution of organic farming to the economy and sustainable development. In pursuing this, statistical data regarding the area under organic farming have been analyzed and correlated to the use of chemical resources. The main findings show that the sector of organic farming has developed in Romania, in the last period. The topic is relevant because organic farming has a double role: social, it develops a specific market that responds to consumers’ demand for organic products, and it provides goods that contribute to the protection of the environment and animal welfare.